Civil disobedience in Indonesia: Legal Notes During the Covid-19 Pandemic 2019 – 2022 - Idaman Idaman; Yusdianto Yusdianto; Jusmang Djalil; Muh. Rizaldi Dirham; Royman M. Hamid; Sri Wulandari (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2024)
Introduction: Covid-19 is an acronym for Coronavirus Disease 2019, which is a virus outbreak that is sweeping the world. virus outbreak that has hit parts of the world, without exception Indonesia, which is one of the affected countries. one of the affected countries. The impact then brings significant changes significant changes to the activities and behaviour of Indonesian citizens, so that the The central to regional governments are taking strategic and concrete steps in order to to alleviate the Covid-19 virus outbreak by limiting people's movement, including implementing social distancing in order to limit social and economic activities in the form of an appeal followed by issuing regulations containing criminal sanctions. issuing regulations that contain criminal sanctions. However, the application of the rules in the public sphere are not obeyed immediately by the public. by the public. This situation creates a shift in the meaning and function of public space, which results in people feeling their movement is restricted in public space. Objective: This paper seeks to elaborate on the factors that contributed to the government's failure to implement its policies during the pandemic, leading to a reaction from civil society in the form of civil disobedience. Methods: The method used in this paper is a literature study, examining a number of data regarding civil disobedience during the covid pandemic in Indonesia. Results: During the covid-19 pandemic in Indonesia, large-scale social restrictions carried out by the government were seen from the lack of preparedness, lack of care, economic protection. As a result, civil society resistance emerged in every government policy related to social distancing. This defiance then resulted in the birth of legal sanctions for civilians who defied government regulations in tackling Covid-19. Keywords: Civil Disobedience; Covid-19; Government policy; Social Distancing